POSSIBILITIES OF ATTENTION IMPROVEMENT FOR ADOLESCENTS - Trubina, Irena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Attention is the ability to focus selectively on a selected stimulus, sustaining that focus and shifting it at will. Attention is important to learning and other cognitive processes. Learning is most efficient when a person is paying attention. Adolescence is a critical transition period, during which fundamental changes prepare the adolescent for becoming an adult. The neurobiology of adolescent behaviour have emerged, promoting the central role of reward and motivation, coupled with cognitive immaturities. It was concluded that maturation and experience are significant in the allocation of attention problems and errors during everyday tasks. The aim was to explore adolescents' attention and to compare two methods of focus for improvement. 24 teenagers take a part in this experiment (16 girls, 8 boys). The teenagers were 12-16 (average age 14, 3).Three groups were created (two groups with different methods and control group). The activities lasted 3 months. The first group of respondents (EGA) practiced the author’s developed methods of playing music in vocal ensemble twice a week, while the other group of respondents (EGB) practiced with computerized equipment CogniPlus. Attention indicators were analysed using the Vienna Test System (SCHUHFRIED) - COG and WAFF tests. Both tests measured various aspects of attention. It was concluded that the EGA group response time statistically significantly improved compared to baseline - 2.28 sec. vs. 1.92 sec. (P = 0.039), but the EGB and CG groups showed no statistically significant differences. In turn, WAFF test, which has to assess to auditory attention reaction time, EGA group has found no statistically significant differences - 0.74 sec. vs. 0.46 sec. (P = 0.002), while EGB are seen only a tendency to improvement in the reaction rate. The results show that although both methods contribute to improvements in attention, however, playing music, influenced by attention statistically significantly. It is planned to continue the study by increasing the number of respondents, as well as the test of attention scores.